Correlation of supplement folic acid based on MTHFR and MTRR gene polymorphisms with preeclampsia in Chinese population: an retrospective cohort study - Xiong, Xuanjun; Xiao, Lin; Xin, Xiaoqin; Huang, Jungao (Frontiers in Nutrition, 2025)
Background and objectivesThe relationship between folic acid supplementation and preeclampsia remains a topic of ongoing debate. We aimed to investigate the correlation between folic acid and preeclampsia from a genetic perspective.MethodsThis retrospective cohort included 377 Chinese participants. We evaluated the risks of eclampsia, including placental growth factor (PIGF) indicators, and the genotypes of folate metabolism markers (MTHFR C677T, MTHFR A1298C, and MTRR A66G). Based on these polymorphisms, participants were categorized into high-risk and relatively low-risk groups, with the high-risk group receiving folic acid supplementation. Multivariate linear and logistic regressions were utilized to calculate the β-coefficients, odds ratios (ORs), and 95% confidence intervals (CIs).ResultsPlGF levels were negatively associated with preeclampsia, with each one-unit increase in PlGF corresponding to a 15% reduction in preeclampsia risk (OR = 0.85, 95% CI: 0.8–0.9), a finding that remained stable across various models. Interestingly, a significant difference was found in PIGF levels between the high-risk group for folic acid and the low-risk group (p = 0.01). Moreover, there was a significantly positive correlation (β = 11.11, 95% CI: 1.68–20.53) and the association persisted across different models, which indicated the high-risk group showed an increase in PIGF concentration when supplementing with folic acid.ConclusionTo our knowledge, limited studies have examined this association at the genetic level in the Chinese population. Our findings suggest that folic acid may mitigate the risk of preeclampsia through its effects on PIGF levels. Potentially, folic acid supplementation could serve as a preventative strategy against preeclampsia.